Socio-Demographic Profile, Knowledge and Awareness Level of Teenage Mothers - Ferdoues, Jannatul; Sultana, Aklima; Akter, Salma; Tyuba Begum, Syeda; Tahmina Sultana, Begum; Noor, Serajun (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Teenage pregnancy is coming up as one of the most important social and public health problem in both developed and developing countries. Lack of knowledge and poor awareness lead to increase number of teenage pregnancy. To assess the knowledge and awareness level of teenage mothers and its consequences. Materials and methods: A cross-sectional observational study was conducted at the Obstetrics and Gynaecology Department of Chittagong Medical College Hospital, Chittagong for a period of six months from 10th October 2013 to 9th April 2014. One hundred teenage mothers (Aged 15-19 completed years at delivery) who got herself admitted to the department of Obstetrics and Gynaecology were included in this study. Predesigned data collections sheet was used and relevant informations were recorded. Results: Among 100 patients, 60 % mothers were in age group of 17-18 years. 25% 19 years, 15% in <17 years. 88% were Muslim, 80% were housewives, 12% garments workers, day laborer 4%, service holder only 1%. Majority of patients (58%) came from low income group families. 26% low middle class, only 6% from upper income group. 60% of mother were upto primary education who had same knowledge about consequence of teenage pregnancy. Can sign only 18%, illiterate 16% who had no knowledge about that. Most of them 64% were unplanned pregnancy. Only 36% were planned. 64% of them never use of any contraceptives. 17% of them use were by herself, used by husband only 6%. Data were analyzed by both manually and by SPSS-18. Conclusion: Teenage are the future of the nation. Not only there should be efforts to improve the socio-demographic environment of pregnant teenagers to improve the reproductive outcome but also decrease the incidence of teenage pregnancy Chatt Maa Shi Hosp Med Coll J; Vol.24 (1); Jan 2025; Page 63-66